CONSEQUENCES OF DYSFUNCTIONAL ANTERIOR GUIDANCE ON THE TEMPORO-MANDIBULAR JOINT - Smaranda Buduru; Daniel Tălmăceanu; Ana Maria Paraschiv; Cosmin Dima (Romanian Society of Oral Rehabilitation, 2019)
Aim: The objective of this study was to establish whether there is a connection between patients with dysfunctional anterior guidance and patients with disc displacements of the temporomandibular joint (TMJ). Materials and methods. In this study a number of 146 participants were included during 2016 to 2018. An anamnestic questionnaire was used and clinical examination of the TMJ and of the occlusion was performed. Inclusion criteria: young subjects with complete, healthy arches. Results. From a total of 146 participants, 82 had disc displacement and 64 did not. In the case of those with disc displacement, 32 had a dysfunctional anterior guidance, and from the ones that had no disc displacement, 17 of them had a dysfunctional anterior guidance. Chi-squared test was used for statistical analysis, from which p>0.05 (p=0.058) and an Odds Ratio of 1.7 were obtained, with a confidence interval (CI) of 0.8-3.6. Conclusions. Patients that were identified to have a risk factor had a 1.7 times higher chance of developing disc displacements. The results of this study have not managed to statistically demonstrate that a dysfunctional anterior guidance has an etiological role in TMJ pathology, but had emphasized a clinical link between patients with a dysfunctional anterior guidance and disc displacements.